Genetic algorithms applied to translational strategy in metabolic-dysfunction associated steatohepatitis (MASH). Learning from mouse models - Martínez-Arranz, Ibon; Alonso, Cristina; Mayo, Rebeca; Mincholé, Itziar; Mato, José M.; Lee, Dae-Jin (Computer methods and programs in biomedicine, 2024)
•Metabolic dysfunction-associated steatotic liver disease (MASLD) is a spectrum of diseases ranging from simple steatosis to metabolic dysfunction-associated steatohepatitis (MASH) and eventually cirrhosis and liver cancer.•A genetic algorithm was applied to a cohort of 541 patients with biopsy-proven MASLD to classify them into two subgroups: M subtype (associated with the MAT1A mouse model) and non-M subtype.•The M subtype cohort was found to have significantly different metabolic profiles than the non-M subtype cohort, which may have important implications for the diagnosis and treatment of diseases associated with this subtype.•The pygenmet package was developed to apply genetic algorithms to metabolic data and select patients with a specific phenotype.•Genetic algorithms can be used to match a patient's genetic profile to others with similar metabolic characteristics, identify disease-causing genes and genetic markers, and develop personalized treatments. We previously identified subsets of patients with metabolic (dysfunction)-associated steatotic liver disease (MASLD) with different metabolic phenotypes. Here, we aimed to refine this classification based on genetic algorithms implemented in a Python package. The use of these genetic algorithms can help scientists to solve problems which cannot be solved with other methods. We present this package and its capabilities with specific problems. The name, PyGenMet, comes from its main goal, solving problems in Python with Genetic Algorithms and Metabolomics data. We collected serum from methionine adenosyltransferase 1a knockout (Mat1a-KO) mice, which have chronically low level of hepatic S-adenosylmethionine (SAMe) and the metabolomes of all samples were determined. We also analyzed serum metabolomes of 541 patients with biopsy proven MASLD (182 with simple steatosis and 359 with metabolic (dysfunction)-associated steatohepatitis or MASH) and compared them with the serum metabolomes of this specific MASLD mouse model using Genetic Algorithms in order to select patients with a specific phenotype. By applying genetic algorithms, we have found a subgroup of patients with a lipid profile similar to that observed in the mouse model. When analyzing the two groups of patients, we have seen that patients with a lipid profile reflecting the mouse model characteristics show significant differences in lipoproteins, especially in LDL-4, LDL-5, and LDL-6 associated with atherogenic risk. The results show that the application of genetic algorithms to subclassify patients with MASLD (or other metabolic disease) give consistent results and are a good approximation for the treatment of large volumes of data such as those from omics sciences and patient classification.